KEMAMPUAN MENGIDENTIFIKASI UNSUR INTRINSIK NOVEL DENGAN TEKNIK INKUIRI SISWA KELAS VIII SMP NEGERI 5 PADANG - Ningsih, Widya; Bahardur, Iswadi; Nisja, Indriani (Pendidikan Bahasa Indonesia, 2013)
Learning literature appreciation in the intrinsic elements of novel with inquiry technique which aims to enable the students to think creatively and solve the problems in learning. This research was motivated by; first, students are less interest to read. Second, students are not motivated to read literary books. Third, students do not understand about the intrinsic elements of novel. Fourth, techniques used by teachers of literature are less attention. This research aims to describe the ability in identifying plot, setting, and characterization by using inquiry technique at eighth grade students of SMP N 5 Padang. Type of this research was quantitative research with descriptive methods. Data analysis was done by the following steps; (1) correcting the results of students answer, (2) treating the score to be value, (3) classifying studentsâ ability by using a scale of 10, (4) determining the mean score, (5) making a histogram based on studentsâ ability, (6)analyzing and discussing the results, (7) concluding the result of analysis.The results of Â were as follows. First, the ability to identify the flow is good in qualifying (86.10). Second, the ability to identify background is good in qualifying (83.27). Third, the ability to identify the characterizations is excellent in qualifying (87.70).